2023
DOI: 10.1159/000531182
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Dysfunction after Atezolizumab and Bevacizumab Is Associated with Favorable Outcomes in Hepatocellular Carcinoma

Abstract: <b><i>Introduction:</i></b> Atezolizumab and bevacizumab (Ate/Bev) combination has become the new first-line systemic therapy for unresectable hepatocellular carcinoma (HCC). Although several studies reported thyroid dysfunction after treatment with immune checkpoint inhibitors, the clinical and immunological significance of thyroid dysfunction in patients treated with Ate/Bev has not been comprehensively addressed. We aimed to comprehensively evaluate the clinical and immunological imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The most commonly documented irAE in our study was an endocrinological disorder, which mainly comprised thyroid-related irAEs. A recent study showed that thyroid-related irAEs occurred in 19.7% of the A + B-treated patients with HCC, which closely aligns with our results of 18% [28]. Given that thyroid-related irAEs require hospitalization to be classified as grade 3 according to the CTCAE criteria, all occurrences of endocrine disorders in our study were categorized as mild irAEs.…”
Section: Effect Of Iraes In Atezolizumab Plussupporting
confidence: 90%
See 1 more Smart Citation
“…The most commonly documented irAE in our study was an endocrinological disorder, which mainly comprised thyroid-related irAEs. A recent study showed that thyroid-related irAEs occurred in 19.7% of the A + B-treated patients with HCC, which closely aligns with our results of 18% [28]. Given that thyroid-related irAEs require hospitalization to be classified as grade 3 according to the CTCAE criteria, all occurrences of endocrine disorders in our study were categorized as mild irAEs.…”
Section: Effect Of Iraes In Atezolizumab Plussupporting
confidence: 90%
“…Bevacizumab-Treated HCC Liver Cancer 2024;13:413-425 DOI: 10.1159/000535839 meticulously explored the frequency and severity of various types of irAEs that can be encountered in real clinical practice among patients with HCC treated with A + B. In this regard, a recent study suggested an association between thyroid-related irAEs and favourable outcomes in HCC patients treated with A + B [28]. Our study further extends this finding by revealing that the occurrence of mild-grade irAEs, encompassing thyroidrelated irAEs, is independently associated with favourable outcomes in terms of OS, PFS, and TTD.…”
Section: Effect Of Iraes In Atezolizumab Plusmentioning
confidence: 99%
“…This finding suggests that the development of thyroiditis may be associated with improved outcomes following atezolizumab/bevacizumab therapy in patients with HCC. 41 In the study by Pinato et al, 42 the steroid dose or duration of use did not significantly affect the survival time or PFS of patients with HCC undergoing immunotherapy.…”
Section: Association Between Iraes and Prognosismentioning
confidence: 90%
“…TrAEs of grade 2 or higher were identified as a predictor of improved OS (hazard ratio [HR], 0.55; 95% CI, 0.34-0.88) and PFS (HR, 0.51; 95% CI, 0.35-0.74) and were associated with a higher ORR of ICI (27% vs. 16%). 40 According to Song et al, 41 patients with thyroid AEs demonstrated significantly better PFS, OS, and ORR than those without thyroid AEs, even after adjusting for confounding factors. This finding suggests that the development of thyroiditis may be associated with improved outcomes following atezolizumab/bevacizumab therapy in patients with HCC.…”
Section: Association Between Iraes and Prognosismentioning
confidence: 99%
“…Hypophysitis is rare following anti-PD-L1 therapy, though reports exist and our RR was elevated [ 29 , 30 ]. Disorders of the thyroid are common following immunotherapy and have been found to show a favourable outcome in hepatocellular carcinoma following atezolizumab treatment [ 31 ]. The incidence of hyperthyroidism and hypothyroidism following anti-PD-L1 therapy is reported to be 0.7% and 3.8–5.5%, respectively, and multiple cases of thyroid disorder post-atezolizumab have been reported [ 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%